HUBUNGAN KOORDINASI MATA-KAKI DAN KELINCAHAN DENGAN KEMAMPUAN DRIBLING PEMAIN SEPAK BOLA SSB GUNUNG TUNGGAL TARAM KECAMATAN HARAU 50 KOTA - Habil .Faruqi; Aldo Naza Putra (Jurnal Muara Olahraga, 2023)
ABSTRACT The problem in this study is that the players' dribbling skills are still not good, it is suspected that it is caused by internal factors, namely the players' physical condition. These physical condition factors include agility, balance, leg muscle strength, leg muscle explosive power, eye-foot coordination, foot contact with the ball and so on. Researchers suspect that the physical condition factor that is considered the most dominant has a relationship and influences the dribbling ability variable, namely eye-foot coordination and player agility. This study aims to reveal the causes of the problems that led to a decline in achievement for the Gunung Tunggal FC Football School (SSB) players, Harau District, 50 Kota District. The purpose of this study was to determine the ability level of speed and ankle coordination on dribbling abilities in Gunung Tunggal FC Football School (SSB) players, Harau District, 50 Kota District. The data collection method uses a test survey method. The data obtained were analyzed using quantitative descriptive statistical analysis. The population of this study were students of the Football School (SSB) Gunung Tunggal FC, Harau District, 50 Kota District. The sampling technique was purposive sampling, namely 26 SSB players. Data collection was carried out by measuring agility variables using the Illinois Agility Run Test, eye and foot coordination tests using the Eye-Foot Coordination Test/kicking the ball to a specified target and dribbling tests using the Dribbling Test. Data processing using multiple correlation There is a significant relationship between agility and Dribbling ability tcount 9.78 > t table 1.72 and r = 0.89. There is a significant relationship between eye and foot coordination on Dribbling ability, the results of calculating t count 5.79 > t table 1.72 and r = 0.76. Agility and Coordination of the eyes and feet on Dribbling ability From the results of data analysis obtained Fcount 10.78 > Ftable, there is a significant relationship between Agility and Coordination of Eyes and Feet together with Dribbling with Rcount = 1.46 Keyword : Agility, Ankle, Dribble, Soccer